Biographical narratives in teaching: A study of professors on postgraduate courses - Carneiro Costa E Silva, Ana Maria (2015)
Literature and research have shown that professional development constitutes an essential dimension in constructing both work and professional identity. An important aspect in such development is training. In the field of adult education, different authors (Pratt, 1993; Mezirow, 1985; Schön, 1996; Silva, 2007) emphasize the importance of placing trainees at the center of the learning and cognitive processes and within their corresponding social and historical contexts. Training is supported by a comprehensive adult learning theory. Therefore, the acquired knowledge is not only the result of an external and objective reality but also of a complex construction in which the appropriation of experience plays a relevant role. This paper reveals the findings obtained through biographical narratives in a five-year work program with teachers at different levels (from preschool to higher education) on postgraduate courses. The core issue is the importance of biographical narratives, as an identification strategy for personal experience, knowledge construction and professional identity. This strategy provided the opportunity for recognition of practical experience, as a provider of learning, as well as his/her own authorship, which are important conditions in the understanding of professional identity.